Retrospective Isotopic Analysis of Summertime Urban Atmospheric Sulfate in South Asia Using Improved Source Constraints - Dasari, S; Widory, D (American Chemical Society, 2024)
The emissions of sulfur dioxide (SO2), a harmful atmospheric pollutant, are on the rise in South Asia. Sulfate, formed from the oxidation of SO2, often comprises 10%–67% of aerosol mass and has a profound impact on climate, air quality/human health, and the environment. The potential drivers of sulfate-linked urban air pollution in South Asian megacitiesfacing a choking air pollution crisisremain poorly understood due to a lack of systematic observations. Here, we conducted stable S-isotope (δ34S) fingerprinting of sulfate aerosols in summertime megacity Delhi in South Asia to evaluate the potential drivers. With newly developed region-specific isotopic endmembers in this study, a statistical source apportionment of urban atmospheric sulfate was feasible. Results show that coal combustion (80 ± 12%) and oil combustion (14 ± 11%), followed by road dust (4 ± 3%) and biomass burning (2 ± 2%), were major contributors to atmospheric sulfate in summertime Delhi. Retrospective analysis showed a marked isotopic shift in stable sulfate isotopic composition in summertime megacity Delhi wherein the average δ34S value was 4 ± 1‰ in 2015 and 2 ± 1‰ in 2021, respectively. This was evidently linked to changes in the dominant fuel type as sulfate sourced from coal combustion (oil combustion) significantly increased ∼ 20% (decreased ∼ 20%) during this period. With no clear increase in the number of thermal power plants in and around Delhi, we speculate that the substantial increase in coal-derived sulfate could plausibly be linked to a rise in the informal industries such as brick production and food and agricultural product processing operations, whose SO2 emissions remain challenging to estimate. While further observations from the region are warranted, the findings here suggest that the continued dependence on coal in developing nations of South Asia could be one of the reasons for rising SO2 levels.